Effect of a weight reduction program on baseline and stress‐induced heart rate variability in children with obesity. (25th December 2015) - Mazurak, Nazar; Sauer, Helene; Weimer, Katja; Dammann, Dirk; Zipfel, Stephan; Horing, Björn; Muth, Eric R.; Teufel, Martin; Enck, Paul; Mack, Isabelle
Abstract : Objective: Autonomic dysregulation is a well‐established feature in adults with obesity but not in children. Since this dysregulation could contribute to weight dynamics, this study aimed to compare autonomic regulation in children with obesity and normal‐weight peers and to track autonomic status during weight reduction. Methods: Sixty children with obesity and 27 age‐ and sex‐matched normal‐weight healthy participants were included. Heart rate variability (HRV) was assessed at baseline and during a mental stress test and a subsequent recovery period. Children with obesity were investigated both upon admission and discharge. Results: Upon admission, no significant differences in HRV parameters were found for normal‐weight participants and those with obesity. Inpatient treatment led to significant changes in HRV with increase in general variability (standard deviation of the normal‐to‐normal interval (SDNN), P  < 0.001) as well as of parasympathetic regulation (root mean square successive difference (RMSSD) and high frequency power (logHF), P  < 0.01). Children with obesity had sympathetic activation similar to normal‐weight controls during mental stress with subsequent return to baseline values, and weight loss did not affect this profile. Conclusions: A weight reduction program induced a change in autonomic activity in children with obesity toward parasympathetic dominance but had no influence on autonomic nervous system reactivity during stress conditions.